Perilous futures on Carl Schmitt's late writings - Hohendahl, Peter Uwe 1936- (Cornell University Press, 2018)
"Offers a sustained critique of Carl Schmitt's late work, especially of his geopolitical theory"...
Includes bibliographical references
Keywords: Schmitt, Carl -- 1888-1985; Political science -- Philosophy -- History -- 20th century; Politische Philosophie